Aplikasi koagulan biji asam jawa dalam penurunan konsentrasi zat warna drimaren red pada limbah tekstil sintetik pada berbagai variasi operasi - Angela Martina; Dian Santoso Effendy; Jenny Novianti M. Soetedjo (Jurnal Rekayasa Proses, 2018)
Since textile industries use a lot of water in their processes, a huge volume of waste water containing dyes are produced by the increase of the production capacity. Coagulation and flocculation are the common processes applied since they can effectively decrease the dye concentration in the waste water. These treatments usually utilize chemical coagulant and flocculant which are expensive and non-biodegradable. In this research, tamarind seed as one of biobased-coagulants was studied and developed to reduce drimaren dark red HF-CD concentration which is used widely in textile industry in the synthetic waste water. The research was designed using Design Expert 7.0.0, Central Composite Design with range of variables as follows: pH (2-7), tamarind seed concentration (1-3 g/L), and dye concentration (20-30 ppm). The result shows a promising application of natural coagulant up to 94.25% decrease of dye concentration in the optimum condition of 3.68 g/L tamarind seed concentration, 25 ppm dye concentration and pH value of 4.5.